2023
DOI: 10.3390/healthcare11141993
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Consequences of War Captivity in Military Veterans

Melita Jukić,
Luka Malenica,
Vanja Đuričić
et al.

Abstract: Numerous studies on the health and functioning of veterans and former prisoners of war have shown that the experience of war captivity is one of the most difficult human experiences. Captivity is often characterized by extremely difficult and inhumane conditions, as well as exposure to various forms of both psychological and physical abuse. Such traumatic experiences can lead to serious psychological consequences that can last for years, even decades after release from captivity. The aim of this paper is to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 102 publications
1
2
0
Order By: Relevance
“…Our research revealed a significant correlation between reduced emotional intelligence and decreased subjective well-being, thereby impeding the efficacy of rehabilitation interventions among POWs. The findings are consistent with Jukić et al [5] study, which demonstrated that psychological and social rehabilitation outcomes were contingent upon the emotional state of POWs.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our research revealed a significant correlation between reduced emotional intelligence and decreased subjective well-being, thereby impeding the efficacy of rehabilitation interventions among POWs. The findings are consistent with Jukić et al [5] study, which demonstrated that psychological and social rehabilitation outcomes were contingent upon the emotional state of POWs.…”
Section: Discussionsupporting
confidence: 91%
“…Difficult experiences in the case of longterm captivity result in a depletion of the desire to continue living as well as suicidal thoughts. Therefore, captivity is considered one of the most difficult experiences of an individual [5]. All military personnel of NATO undergo the SERE (Survival, Evasion, Resistance, Escape) course as part of basic training, which is aimed at learning survival skills in the event of captivity as well as reducing stress thereafter [11].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation